Embelin Prevents Seizure and Associated Cognitive Impairments in a Pentylenetetrazole-Induced Kindling Zebrafish Model - Kundap, Uday Praful; Paudel, Yam Nath; Kumari, Yatinesh; Othman, Iekshan; Shaikh, Mohd. Farooq (Frontiers in Pharmacology, 2019)
Epilepsy is a neuronal disorder associated with several neurological and behavioral alterations characterized by recurrent spontaneous epileptic seizures. Despite having more than 20 anti-epileptic drugs (AEDs), they only provide a symptomatic treatment. As well as, currently available AEDs also displayed cognitive alterations in addition to retarding seizure. This leads to the need for exploring new molecules that can not only retard seizure but also improve cognitive impairment. Embelin (EMB) is a benzoquinone derivative which has already demonstrated its pharmacological potentials against arrays of neurological conditions. Current study developed a chronic kindling model in adult zebrafish by using repeated administration of small doses of pentylenetetrazole (PTZ) and by a single dose of Kainic acid (KA) to investigate the associated memory impairment. This has been done by using the three-axis maze which is a conventional method to test the learning ability and egocentric memory in zebrafish. As well as, the ameliorative potential of EMB has been evaluated against chronic epilepsy-related memory alterations. As well as the expression level of pro-inflammatory genes such as C-C motif ligand 2 (CCL2), toll-like receptor-4 (TLR4), tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1) and interferon-γ (IFN-γ) were evaluated. Level of several neurotransmitters such as γ-aminobutyric acid (GABA), acetylcholine (Ach) and glutamate (Glu) was evaluated by liquid chromatography-mass spectrometry (LC-MS). The results showed that daily dose of PTZ 80 mg/kg for 10 days successfully induces a kindling effect in zebrafish, whereas the single dose of KA did not. As compared to control, PTZ and KA group demonstrates impairment in memory as demonstrated by three-axis maze. PTZ group treated with a series of EMB doses ranging from (0.156 mg/kg to 0.625) retards seizure as well as significantly reduces epilepsy-induced memory alteration. In addition, EMB treatment reduces the expression of inflammatory markers implicating its anti-inflammatory potential. Moreover, levels of GABA, Ach, and glutamate are increased in EMB administered group as compared to the PTZ administered group. Overall, findings demonstrate that EMB might be a potential candidate against chronic epilepsy-related cognitive dysfunction as EMB prevents the seizures, so we expect it to prevent the associated neuroinflammation and learning deficit.